Pancasila dan Artificial Intelligence: Analisis Etis atas Regulasi AI di Indonesia: Pancasila and Artificial Intelligence: Ethical Analysis of AI Regulations in Indonesia - Inayah Ma’unah; Safitri Musyarofah; Al Fiola Zulfah Az Zahra; Yenitasari Agrariyanti (Litera Academica Publishing, 2025)
The rapid advancement of artificial intelligence (AI) has profoundly transformed various aspects of human life but also presents complex ethical, legal, and social challenges. As a nation founded on Pancasila, Indonesia must ensure that AI regulation is not merely technical but also aligned with its foundational values. This study aims to conceptually and argumentatively analyze the integration of Pancasila principles into AI regulation in Indonesia, identify existing challenges, and propose a relevant regulatory framework. The research employs a normative-philosophical literature review approach, drawing from both national and international sources. The findings reveal that Indonesia’s current AI regulations remain fragmented and fail to comprehensively address ethical dimensions. Four major challenges were identified: legal gaps, algorithmic bias, privacy violations, and low digital literacy. Integrating Pancasila values into five dimensions — normative, juridical, technical, institutional, and social — can provide a foundation for fair, inclusive, and sovereign AI governance. The study concludes that Pancasila plays a crucial role in guiding AI governance to not only advance technology but also strengthen social justice and humanity.